Empowering Community Health Workers in Tuberculosis Prevention Through Settlement Sanitation Improvement - Erni Buston; Efrizon Hariadi; Pauzan Efendi; Mercy Nafratilova; Mualim, Mualim (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2024)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. The purpose of this Community Service activity is to improve healthy houses and healthy settlements in the prevention of TB disease in the Lempuing and Sawah Lebar Baru Health Center areas. Based on the analysis of the situation above, the problems in the working area of the Lempuing and Sawah Lebar Baru Health Centers can be identified as follows: the high number of TB cases in the working area of the Lempuing and Sawah Lebar Baru Health Centers, the low knowledge about residential sanitation, the dangers and health impacts caused, the low knowledge about the dangers of TB disease transmission, the low level of knowledge about PHBS. This method of community service activities uses the method of community empowerment and community participation with a family nursing approach through problem recognition, deciding to take care of, take care of it, modify the environment and utilize health facilities. Evaluation of activities and monitoring is carried out formatively and summatively through the instruments that have been prepared. The results of the Wilcoxon Ranked Test statistical test showed a p value of 0.000 (p value ≤ α = 0.05), meaning that there was an influence of knowledge and skills after community service.